(untitled) (Journal of actual problems of jurisprudence, 2022)
The article explores the issues of higher education quality in the context of global changes, taking into account the legal framework, which emphasizes the relevance of research. The approach to study the impact of international trends on the quality of higher education institutions, the level of educational services and the demand for graduates in the labor market is of scientific interest. The purpose of the study is to validate the interaction of global trends on the quality of academic services, to identify the problems of quality of higher education, the specific features of the transformation of education and to determine the main guidelines to improve their competitiveness. Ongoing monitoring and comparative analysis have indicated that in order to improve the quality of education in higher education institutions it is essential to continue further targeted work in accord with international quality standards, which will facilitate the entry into the world educational space. The study is descriptive and sequential, from simple to complex, which examines the essence of the quality education concept, presents development stages of this category, examines legislative support, formation of independent evaluation of HEIs and study programmes, which allows to determine the critical role and particular importance of promoting quality culture in higher education institutions. The study proposes to develop an annual Action Plan for the implementation of the University Development Strategy, taking into account risk management, which will allow universities to improve the quality of educational programmes and increase the competitiveness of graduates. The study advances knowledge in the area of international accreditation and provides insight to management, faculty, students and stakeholders on the challenges of implementing international standards and external quality assurance in education. Key words: globalisation, quality of education, legal assurance, accreditation.